The UTAUT Implementation Model in Defining the Behavioral Intention of Mobile Banking Users - Handayani, Wahyu Prabawati Putri (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This goal is to comprehend how the UTAUT model was used to influence mobile banking behavior intentions and act as a mediator variable along with attitude.Design/Methodology/Approach: A quantitative approach and a sample size of 110 respondents using mobile banking were used. The deployment questionnaire for the retrieval technique sample was completed using Google Forms, and the sampling strategy was a snowball. In this study, both data analysis and hypothesis evaluation were performed utilizing PLS-SEM.Research findings: The study uncovered that out of ten hypotheses, seven were accepted, and three were rejected. In this study, performance expectancy, facilitating conditions, and social influence variables could all have an impact on attitude. With regard to behavioral intention, attitude served as a mediator between performance expectancy, social influence, and facilitating conditions. Aside from serving as a mediator, the attitude directly affected behavioral intentions. The results indicate that attitude was not significantly affected by effort expectations, and behavioral intentions were not significantly impacted by trust.Theoretical Contribution/Originality: The Unified Theory of Acceptance and Use of Technology (UTAUT) was employed in this study to understand better how the UTAUT model was applied in influencing mobile banking behavior intentions, as well as how attitude functions as a variable mediator.Practitioners/Policy Implications: Results from the study have implications for how mobile banking users' behavioral intentions may change depending on their performance expectancy, social influence, facilitating conditions, and attitudes.Research Limitations/Implications: Further research is required to observe other aspects, such as the desire to keep utilizing mobile banking, as it is the focus of this study, which was restricted to behavioral intention based on the considerations of UTAUT-based mobile banking users.